Author Correction: A comprehensive model for assessment of liver stage therapies targeting Plasmodium vivax and Plasmodium falciparum - Alison Roth (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of Richard Thomson-Luque, which was incorrectly given as Richard Thomson Luque. This error has now been corrected in both the PDF and HTML versions of the Article.